The alternative oxidases: simple oxidoreductase proteins with complex functions. (23rd September 2013) - Young, Luke; Shiba, Tomoo; Harada, Shigeharu; Kita, Kiyoshi; Albury, Mary S.; Moore, Anthony L.
Abstract : The alternative oxidases are membrane-bound monotopic terminal electron transport proteins found in all plants and in some agrochemically important fungi and parasites including Trypansoma brucei, which is the causative agent of trypanosomiasis. They are integral membrane proteins and reduce oxygen to water in a four electron process. The recent elucidation of the crystal structure of the trypanosomal alternative oxidase at 2.85 Å (1 Å=0.1 nm) has revealed salient structural features necessary for its function. In the present review we compare the primary and secondary ligation spheres of the alternative oxidases with other di-iron carboxylate proteins and propose a mechanism for the reduction of oxygen to water.